Fleet planning and technology upgrade projects: supporting decision-making through visualisation. (2018) - Kerr, Clive; Ford, Simon
In project planning, visualisations can be powerful tools for communication and in supporting decision-making between stakeholders. However the graphical elements, in terms of form and presentational style, are typically poorly treated and can therefore diminish both the impact and conveyance of information. Traditional timeline representations need to be adapted and modified in order to meet the requirements of specific stakeholder groups and thus fulfil their role as effective visual boundary objects. This paper describes the visualisation designed and developed for the planning of technology upgrade projects across a fleet of military platforms. A real-world application of the visualisation is provided through an illustrative case study based on the front-line fleet of Type 23 frigates of the Royal Navy.